The Medical Informatics Program at the National - University of Singapore - Lun, K.C.; Leong, T.Y.; Ong, Kenneth; Raghavan, R.; Pung, H.K. (Yearbook of Medical Informatics, 1998)
The Medical Informatics Program at the National University of Singapore was established in September 1996 with a $4 million joint funding from the National Science and Technology Board and the Ministry of Education. The primary aims of the research program are to undertake upstream basic research in medical informatics and to build a critical mass of medical informatics expertise to meet long-term research goals and to effect technology transfer to the health sector of Singapore. Research projects fall into five groups: Clinical Decision Systems, Health Information Systems, Biomedical Datamining Systems, Medical Education Systems and Medical Networking, Applications Development and Integration Systems.
Keywords: Education; Clinical Decision making; Data Mining